Partisipasi Publik dan Konstruksi Citra: Strategi Community Relations Berbasis Komunitas Railfans di Tingkat Operasional Perkeretaapian - Audeline Putri Pramesya; Anggun Anindya Sekarningrum (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
This study aims to analyze the community relations strategy implemented by the Public Relations unit of PT Kereta Api Indonesia (Persero) Daerah Operasi (Daop) 3 Cirebon in enhancing corporate image through the involvement of railfans communities. This research employs a qualitative approach with a case study method. Data were collected through in-depth interviews with internal stakeholders from the Public Relations unit of PT KAI Daop 3 Cirebon and representatives of railfans communities, including the Indonesian Railways Preservation Society (IRPS) Cirebon Region, Edan Sepur Cirebon Community, and Railfans Daop 3 Community (KRD3), supported by documentation of activities. The findings indicate that the community relations strategy is implemented in a structured and continuous manner, starting from community mapping and planning, collaborative program implementation, to evaluation. The activities include level crossing safety campaigns, sexual harassment prevention socialization in station areas and train services, involvement of railfans in Eid and Christmas–New Year transportation posts, passenger service support, environmental cleanliness programs at stations, and participation in the inauguration of railway facilities and infrastructure. The involvement of railfans communities as strategic partners strengthens message credibility, increases public participation, and contributes to the formation of a positive corporate image of PT KAI Daop 3 Cirebon as an open, responsif, and socially responsible public transportation company. This study implies that participatory and collaborative community relations strategies play a significant role in strengthening corporate image at the regional operational level.